INOVASI MEDIA DIGITAL DALAM PEMBELAJARAN FIQIH - SELSA CAHAYA (CV. ADIBA ASIHA AMIRA, 2026)
This study examines the use of digital media innovation in improving fiqh learning. Using a qualitative literature review approach, the findings show that digital media such as interactive videos and e-learning platforms enhance students’ understanding and motivation. However, challenges such as limited digital literacy and technology misuse need to be addressed through proper integration with Islamic values.